Microwave-assisted synthesis of 5-substituted 1H-tetrazoles via [3+2] cycloaddition over a heterogeneous Cu-based catalyst: application to the preparation of N-13-labelled tetrazoles - Joshi, Sameer M.; Mane, Rasika B.; Pulagam, Krishna R.; Gomez-Vallejo, Vanessa; Llop, Jordi; Rode, Chandrashekhar (New Journal of Chemistry, 2017)
The [3+2] cycloaddition between various nitriles and sodium azide proceeds smoothly in the presence of a new Cu-II catalyst in N-methyl-2-pyrrolidone (NMP) to give the corresponding 5-substituted 1H-tetrazoles. The desired tetrazoles were obtained in high yields within 3-30 min by employing controlled microwave heating. The reaction most probably proceeds through the activation of the nitrile groups by the Cu-II species, followed by a successive [3+2] cycloaddition with the sodium azide. The good performance of the catalyst enabled the preparation of selected tetrazoles labelled with the positron emitter nitrogen-13 even under conventional heating. The short reaction time, simple work-up procedure, and recyclability of the catalyst are advantages of the method reported here.

Mixed bacterial culture mediated direct conversion of bio-glycerol to diols - Parate, Roopa; Mane, Rasika; Dharne, Mahesh; Rode, Chandrashekhar (Bioresource Technology, 2018)
Direct and economic transformation of biodiesel derived crude glycerol is gaining more significance. During screening of bacterial cultures Klebsiella pneumoniae and Enterobacter aerogenes were able to convert crude bio-glycerol to 2,3-butanediol (2,3-BDO) and 1,3-propanediol (1,3-PDO), as major compounds, ethanol and acetoin as minor compounds, with a conversion of 69% and 79% respectively. Process optimization could achieve maximum conversion at pH 7.0, 37 degrees C, 30-40 g/L glycerol and 1.5 g of inoculum until 120 h. Mixed cultures led to complete glycerol conversion with optimal yield and productivity. An innovative approach of using crude glycerol for sustained growth and tolerance of bacteria as source of carbon and energy makes this study more significant. In addition to this, a mixed culture concept introduced here is expected to make impact in process economics for industrial scale synthesis for direct transformation of glycerol into C3 and specifically, C4 diols.
Keywords: 1; 2; 3-Butanediol; 3-Propanediol; Bioconversion; Bioglycerol; Mixed culture

Magnetically separable catalyst for condensation of renewable aldehydes and 2-methylfuran to saturated cyclic oxygenates - Tarade, Komal; Shinde, Suhas; Rode, Chandrashekhar (Fuel Processing Technology, 2020)
The saturated cyclic ethers produced from biomass derived aldehydes and 2-methylfuran are the potential diesel fuel candidates. The synthesis of saturated cyclic ethers is a two step process which involves acid catalyzed condensation of aldehydes with 2-methylfuran and the subsequent selective furan ring hydrogenation of the condensation products. Here, we designed a novel recyclable magnetic solid acid catalyst such as [Fe3O4@SiO2-Pr-Py-H][2HSO(4)(2-)] and employed for the condensation of 2-methylfuran with formaldehyde as model substrates and reaction parameters were optimized. Under the set reaction conditions, condensation of 2-methylfuran with several other aldehydes were also successfully achieved with very good yields. Further, several supported noble metal catalysts were screened in order to find suitable catalyst system for selective furan ring hydrogenation of condensation products. Among those, 5% Pd/C was found to be very active and selective for furan ring hydrogenation without formation of ring opened products under very low hydrogen pressure at room temperature. Prepared catalysts were thoroughly characterized with sophisticated techniques.
Keywords: fuel additives; Hydrogenation; Hydroxyalkylation-alkylation; Magnetic solid acid; Organosilica

Mechanical properties of anodic titanium dioxide nanostructures - Kulkarni, Mukta; Sepitka, Josef; Junkar, Ita; Bencina, Metka; Rawat, Niharika; Mazare, Anca; Rode, Chandrashekhar; Gokhale, Suresh; Schmuki, Patrik; Daniel, Matej; Iglic, Ales (Materiali in Tehnologije, 2021)
Highly ordered and uniform titanium dioxide (TiO2) nanotubes (NTs) with different morphologies (15 nm, 50 nm and 100 nm in diameter) were prepared by the electrochemical anodization of Ti substrates. The TiO2 NTs' surface properties were characterized by X-ray diffraction (XRD) spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM). The elastic modulus (E) and the Vickers hardness (HV) of the Ti foil and of the different-morphology TiO2 NTs were evaluated with the nano-indentation technique. E and HV increase with the decreasing length/diameter of the NTs, meaning that NTs with smaller diameters are more resistant to mechanical wear. The elastic modulus of the TiO2 NTs with 15-nm and 50-nm diameters is similar to that of the human bone.
Keywords: Elastic modulus; mechanical properties; titanium dioxide (TiO2) nanotubes; Vickers hardness

Magnetically separable Brønsted acid catalyst for the synthesis of Bisguaiacol-F - Tarade, Komal; Rode, Chandrashekhar; Kamble, Sanjay (New Journal of Chemistry, 2025)
Currently, polycarbonates, epoxy resins, and plastics are commercially made from Bisphenol-A. However, BPA-containing materials are well known for causing major health problems and have been banned in several countries. To address this concern, Bisguaiacol-F (BGF) has been developed as a safer and more sustainable alternative to Bisphenol-A. We created a novel sulfonic acid-functionalized, magnetically separable heterogeneous Br & oslash;nsted acid catalyst, [Fe3O4@SiO2-(Pr)3-N-Bu-SO3H][HSO4-], which was successfully utilized for the manufacture of BGF by condensing 37% aq. formaldehyde with two molecules of guaiacol. The main objective for this reaction was to avoid using excess guaiacol while also completing the conversion of both starting components. Surprisingly, our manufactured catalyst promotes the complete conversion of aqueous formaldehyde and guaiacol into regioisomers such as pp `-BGF, mp `-BGF and op `-BGF with 62%, 15%, and 6% selectivity, respectively. Our novel magnetically separable heterogeneous catalyst has improved catalytic activity in terms of starting material conversion and product distribution, which can be attributed to its unique structural characteristics. It contains a pendant -SO3H group that is connected to a lengthy butyl chain, making it conveniently accessible in the reaction. We have created the framework for a promising and environmentally aware approach to the synthesis of Bisguaiacol-F by meticulously optimizing reaction parameters such as time, temperature, reactant molar ratio, and catalyst loading. The catalyst was extensively characterized using acid-base titration, FT-IR, XRD, TGA, and NMR techniques to confirm the structure and reveal remarkable stability and activity. Notably, the catalyst demonstrated recyclability across six consecutive runs, with no noticeable reduction in its effectiveness. The catalytic activity was also tested for guaiacol condensation with a variety of aldehydes to create Bisguaiacol derivatives.